Efficacy and Safety of GLP-1 Receptor Agonists Across the Spectrum of Type 2 Diabetes Mellitus - Leiter, Lawrence A.; Nauck, Michael A. (Experimental and Clinical Endocrinology & Diabetes, 2017)
For patients with type 2 diabetes mellitus, glucagon-like peptide-1 receptor agonists (GLP-1RAs) generally exert robust glucose-lowering effects that are at least as effective as insulin. As monotherapies, changes from baseline in HbA1c with GLP-1RAs ranged from –1.9 to –0.7% in phase 3 trials. In addition, GLP-1RAs confer a low risk of hypoglycaemia and have a body-weight advantage (changes from baseline ranging from –4.0 to –0.4 kg). There is also evidence of significant reductions in risk for cardiovascular events with some of these agents, with a number of other trials underway. Gastrointestinal adverse events typically increase with GLP-1RAs, although these are generally mild to moderate in intensity and rarely require treatment discontinuation. The GLP-1RAs that are commercially available or in development vary in structure and pharmacokinetics. These differences affect the frequency of administration and can also affect their relative efficacy and safety. This review summarizes the findings of phase 3 glycaemic control trials of available GLP-1RAs and considers them in the context of the distinct clinical needs of individual patients.
Keywords: glucagon-like peptide-1; hyperglycaemia; hypoglycaemic agents; incretins; type 2 diabetes mellitus